The Arteriography in diagnosis of chronic osteomyelitis of limbs. - Vanrell, Rafael; Silva, Celso (Cirugía del Uruguay, 1976)
Arteriography in cases of chronic osteomye!itis is rare and is only justified when diagnosis is doubtful. It is not infalible in its conclusions, but it does make it possible to differenciate this condition from the majority of pathological processes of the bone. The authors describe the. characteristics of the arteriographic and phlebographic phases of this procedure, together with case mater-a1 covering 7 cases, in one of which it served to establish an early diagnosis of this disease.